HISTORY OF MEDICINE : HISTORY OF EPILEPSY - Cabral Barbosa, Alice; de Oliveira Arantes, Arthur; de Almeida Sousa, Jéssica; Carolina Rios Fonseca, Maria; Mitsue de Castro Matsuoka, Sarah (Health and Society, 2022)
The objective of this article is to approach the main historical milestones of epilepsy, a disease that affects 50 million people in the world, 40 million of them in developing countries. An important part of the sick population does not deal with treatment, although it is a predominantly controllable problem. Probably one of the main causes for this is the stigma that attends people with epilepsy.